AN INTEGRATED NETWORK ANALYSIS OF PSORIASIS: A NOVEL APPROACH TO DISEASE PATHOLOGY - Anand D, Alex; Harishchander A; Jason Ub (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: Psoriasis is a chronic autoimmune disorder. At present, about 2% of human population is affected by psoriasis in a global scale. There is no permanent cure for psoriasis in the post-genomic era and the disease mechanism too is poorly understood. We hereby investigate psoriasis through a systems biology approach to identify the underlying regulatory networks, which are pivotal to the disease pathology of psoriasis. Methods: Initially, we surveyed microarray studies from array express, and then we extracted the list of implicated genes through array mining tools. We then verified the nomenclature of extracted genes and extracted gene ontology information from various publications and databases such as UCSC, HUGO, and DAVID. We then have identified the list of novel micro RNA (miRNAs), transcription factors and pathways, which are involved in the disease pathology of psoriasis from EnrichR. Results: EnrichR predicted 193 miRNAs, 183 transcription factors, and 116 pathways. After applying various mining techniques and statistics, we identified a very few transcriptions factors and miRNAs, which are related to the disease pathways of psoriasis. Finally, we have used t-test to identify a specific miRNA and transcription factors, which are associated with the disease pathology of psoriasis on the basis of pathway analysis and it was identified that hsa-miR-324-5p and PAX3 have a higher degree of association on the basis of p-value. Conclusion: Integrated network analysis of biological data is an exciting view point to view and understand the pathological conditions in a biological system, but until date this field has not developed enough to encompass etiology and therapy. In order to take an equilibrium shift from the level of disease understanding to pattern characterization and therapy, there is a requirement for conducting more experimental studies on human with the respective ailments. At present, we have applied the approach of network analysis to psoriasis and in future we will be applying this approach to understand the disease pathology of various disorders of autoimmune nature. Keywords: Psoriasis, Micro RNA, Post-genomics, Bioinformatics and systems biology.